Audit on flexible sigmoidoscopy for rectal bleeding in a district general hospital: are we over-loading the resources?. Issue 939 (3rd February 2004) - Mathew, J; Shankar, P; Aldean, I M
Abstract : Objective: Patients with rectal bleeding are being over investigated because of the fear of missing colorectal cancers. This study aimed to identify the percentage of patients <45 years of age who undergo flexible sigmoidoscopy for rectal bleeding, and to assess and compare the incidence of colorectal cancers and polyps above and below this age. Methods: Patients who underwent flexible sigmoidoscopy for rectal bleeding between 1 January 2000 and 31 December 2002 were reviewed. Patients were divided into two groups: group 1 consisted of patients aged ⩾45 years and group 2 patients <45 years. The histopathology of biopsy specimens taken was also studied. Results: Altogether 18.9% of the patients who had flexible sigmoidoscopy for rectal bleeding were <45 years. The incidence of colorectal cancers in group 1 was 3.5%; all these cases were confirmed on histopathology. Only one patient in group 2 was diagnosed with colorectal cancer on flexible sigmoidoscopy, but the histopathology disproved it. The incidence of polyps was 16.6% in group 1 and 7.9% in group 2. Following histopathology, the incidence of adenomatous polyps was 6.8% in group 1 and 2.1% in group 2. There was a significant difference between the two groups, with a p value of <0.0001. Conclusion: The incidence of colorectal cancers and adenomatous polyps in patients aged <45 years with rectal bleeding is very low. A flexible sigmoidoscopy costs approximately £330. If new guidelines are implemented considering the age of the patient, considerable cost savings could be made, and the available resources could be appropriately used in groups with high incidences of colorectal cancers.